2015
DOI: 10.1097/ico.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Ultrastructural Characteristics of Graft Failure in DMEK

Abstract: A preexisting subclinical corneal endothelial dysfunction may contribute to primary DMEK failure. Repeat DMEK can be performed safely with good long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
3
30
0
2
Order By: Relevance
“…In the paired analysis made by Price et al , the interval between primary and repeat DMEK ranged between 2 and 133 days (median=21 days), whereas both in the study by Baydoun et al 7 and in that by Ćirković et al, 8 the interval was much longer, ranging in the former series between 4 and 33 months, and in the latter series between 7 and 497 days. As early reintervention is crucial in order to optimise visual recovery, waiting for the cornea to clear does not seem to be justified beyond few weeks, even if late recovery of transparency may occasionally occur even in the presence of graft detachment 9…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the paired analysis made by Price et al , the interval between primary and repeat DMEK ranged between 2 and 133 days (median=21 days), whereas both in the study by Baydoun et al 7 and in that by Ćirković et al, 8 the interval was much longer, ranging in the former series between 4 and 33 months, and in the latter series between 7 and 497 days. As early reintervention is crucial in order to optimise visual recovery, waiting for the cornea to clear does not seem to be justified beyond few weeks, even if late recovery of transparency may occasionally occur even in the presence of graft detachment 9…”
Section: Discussionmentioning
confidence: 89%
“…Also Ćirković et al 8 in a recent publication reported that repeating DMEK is safe but yields results worse than those recorded after primary DMEK. In this series, 1 year after surgery no eye without comorbidity could see 20/20 and only 2 of 15 (13.3%) eyes could see 20/25.…”
Section: Discussionmentioning
confidence: 98%
“…Repeat DMEK was performed safely with good long-term outcome, which agrees with the results of other studies. 37,38 In conclusion, given the better results in terms of graft detachment with similar clinical outcomes and corneal endothelium survival, tamponade with 20% SF 6 currently is our standard technique for all cases of DMEK. Longer-term, randomized studies are needed to recommend its routine use in DMEK fully and safely.…”
Section: Discussionmentioning
confidence: 93%
“…In another study, we recently found that the size of the descemetorhexis also has an influence on graft adherence. 23 Other known significant factors include preexisting graft damage, 27 intraoperative trauma, 27 and, as mentioned before, surgeon experience. 28,29 According to our clinical experience, the amount of intraoperative rolling and the ease of graft insertion and its fragility all depend on donor age.…”
Section: Discussionmentioning
confidence: 98%